β lactam monotherapy versus β lactam-aminoglycoside combination therapy for fever with neutropenia: systematic review and meta-analysis - Paul, Mical (BMJ Publishing Group Ltd., 2003)
Objective To compare the effectiveness of β lactam monotherapy versus β lactam-aminoglycoside combination therapy in the treatment of patients with fever and neutropenia. Data sources Medline, Embase, Lilacs, the Cochrane Library, and conference proceedings to 2002. References of included studies and contact with authors. No restrictions on language, year of publication, or publication status. Study selection All randomised trials of β lactam monotherapy compared with β lactam-minoglycoside combination therapy as empirical treatment for patients with fever and neutropenia. Data selection Two reviewers independently applied selection criteria, performed quality assessment, and extracted data. An intention to treat approach was used. Relative risks were pooled with the random effect model. Main outcome measure All cause fatality. Results Forty seven trials with 7807 patients met inclusion criteria. Nine trials compared the same β lactam. There was no significant difference in all cause fatality (relative risk 0.85, 95% confidence interval 0.72 to 1.02). For success of treatment there was a significant advantage with monotherapy (0.92, 0.85 to 0.99), though there was considerable heterogeneity among trials. There was no significant difference between monotherapy and combination treatment in trials that compared the same β lactam, whereas there was major advantage with monotherapy in trials that compared different β lactams (0.87, 0.80 to 0.93). Rates of superinfection were similar. Adverse events, including those associated with severe morbidity, were significantly more common in the combination treatment group. Detected flaws in methods did not affect results. Conclusions For patients with fever and neutropenia there is no clinical advantage in treatment with β lactam-aminoglycoside combination therapy. Broad spectrum β lactams as monotherapy should be regarded as the standard of care for such patients.